Comparison of Phenolic Contents and Scavenging Activities of Miang Extracts Derived from Filamentous and Non-Filamentous Fungi-Based Fermentation Processes - Aliyu Dantani Abdullahi; Pratthana Kodchasee; Kridsada Unban; Thanawat Pattananandecha; Chalermpong Saenjum; Apinun Kanpiengjai; Kalidas Shetty; Chartchai Khanongnuch (MDPI AG, 2021)
The study investigated the impact of the fermentation process on the phenolic contents and antioxidant and anti-inflammatory activities in extracts of Miang, an ethnic fermented tea product of northern Thailand. The acetone (80%) extraction of Miang samples fermented by a non-filamentous fungi-based process (NFP) and filamentous fungi-based process (FFP) had elevated levels of total polyphenols, total tannins, and condensed tannins compared to young and mature tea leaves. The antioxidant studies also showed better the half-maximal inhibitory concentration (IC50) values for fermented leaves in both 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging activity assays as well as improved ferric reducing antioxidant power (FRAP) compared to young and mature tea leaves. Extracts of NFP and FFP samples at concentrations of 50 and 100 ppm showed better protective effects against hydrogen peroxide (H2O2)-induced intracellular reactive oxygen species (ROS) production in HT-29 colorectal cells without exerting cytotoxicity. Additionally, lipopolysaccharide (LPS)-induced production of nitric oxide (a proinflammatory mediator as well as a reactive nitrogen species) was also inhibited by these fermented Miang extracts with an IC50 values of 17.15 μg/mL (NFP), 20.17 μg/mL (FFP), 33.96 μg/mL (young tea leaves), and 31.33 μg/mL (mature tea leaves). Therefore, both NFP-Miang and FFP-Miang showed the potential to be targeted as natural bioactive functional ingredients with preventive properties against free radical and inflammatory-mediated diseases.